Feminist Climate Policy in Industrialised States (Taylor & Francis, 2025)
Feminist Climate Policy in Industrialised States explores ways in which policymakers can overcome institutional barriers and conventions in pursuit of the radical changes necessary for a gender-just climate emergency response. In 2021, the Intergovernmental Panel on Climate Change acknowledged that addressing the climate emergency must involve social justice and equality. Feminist approaches to decision-making, policy-making, community organising and their underpinning methodologies can enable this. The authors draw critically on case studies, research and interviews with feminist practitioners, legislators and leaders who have implemented significant changes, to signal how change might be achieved and ask what lessons can be drawn. The book posits that we need to ultimately move beyond the gender mainstreaming and gender equality issues which have been integrated into existing – and failing – structures, to more transformative feminist approaches. It concludes by identifying key strands of feminist-oriented praxis that offer the potential to expedite responses to climate change across multiple levels of governance. With industrialised states shifting rightwards to a politics which diminishes the importance and urgency of gender equality, diversity, human rights and the need for climate action, this volume will inspire, guide, and provide tools for policymakers, politicians, community activists, academics, and students to take transformative action to address the climate emergency. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.